The level of matrix metalloproteinase-9 in the serum as a prognostic sign in extrasphincteric fistulas of the rectum - I. Mishura, Zoya; K. Paliyenko, Ruslan; R. Kerbazh, Nizar (International Journal of Medicine, 2021)
Background. Acute or chronic rectal fistulas make up to 30% of proctologic pathology and are accompanied by significant impairment of patients` lives. In recent years, the role of matrix metalloproteinases in the pathogenesis of many diseases has grown rapidly. The most widely expressed protease in inflamed tissues is matrix metalloproteinase-9 (MMP-9).Objectives. To identify and analyze changes in the level of MMP-9 in the serum of patients with extrasphincteric fistulas of the rectum, depending on the method of surgery.Methods. The study involved 28 patients with extrasphincteric rectal fistulas, who undergone surgery in the proctology department of Poltava Regional Clinical Hospital and the surgical department of the 3rd city clinical hospital in Poltava from 2010 to 2018. The patients were divided into 2 groups according to the method of surgical treatment. Quantitative determination of MMP-9 in blood serum was performed.Results. In the main group, the average value of MMP-9 before surgery was 14.90 Â± 0.15 ng/ml, a month later it decreased to 7.73 Â± 0.37 ng/ml (pË‚0.0001), and after three months, the average value of MMP-9 was determined at 2.41 Â± 0.13 ng/ml (pË‚0.0001). In the comparison group, the initial average value was 15.00 Â± 0.08 ng/ml, which decreased to 11.89 Â± 0.26 ng/ml (pË‚0.0001), and three months after surgery it decreased to 4.14 Â± 0.17 ng/ml (pË‚0.0001).Conclusion. The use of MMP-9 levels in blood serum before and after surgery has determined that the method of treatment of extrasphincteric fistulas using the drug Tachocomb is less traumatic and reduces the healing time of postoperative wounds compared to the ligature method.Â Â Â